Comparison of wind-driven rain load on building facades in the urban environment and open field: A case study on two buildings in Zurich, Switzerland. (1st April 2023) - Zhou, Xiaohai; Kubilay, Aytaç; Derome, Dominique; Carmeliet, Jan
Abstract: Wind-driven rain (WDR) is one of the largest moisture sources affecting the hygrothermal performance and durability of building envelopes. Accurate estimation of WDR loads on building facades as boundary condition is important for the hygrothermal analysis of building envelopes. In this work, computational fluid dynamics (CFD) simulations and semi-empirical models are used to compare WDR load on building facades in the urban environment and open field. The research focuses on two historical buildings in the city center of Zurich, Switzerland. There is a very large difference in terms of the local wind-flow fields around buildings in the urban environment and open field. Raindrop trajectories in the open field are more horizontal due to higher wind speeds around the building. In the urban environment, the wind speed is lower yielding droplets following trajectories that are more parallel to the facades. The building overhang is more effective at rain protection in the urban environment compared to the building in the open field due to a larger rain sheltering effect, since the rain trajectories are more parallel to the facades. There is a very large difference in WDR load and distribution on the facade of buildings in the urban environment and open field. WDR loads on buildings in the urban environment are much smaller than in the open field. When semi-empirical models are used for this case study, there is large uncertainty in the prediction and the predicted WDR load can be many times larger compared to the load predicted by CFD. Highlights: WDR simulation in the urban environment and open field is performed. WDR load on buildings in the urban environment is smaller than in open field. There is a large uncertainty in the prediction of WDR by semi-empirical models.